My Brain Needs a Break: Kindergarteners’ Willpower Theories Are Related to Behavioral Self-Regulation - Compagnoni, Miriam; Sieber, Vanda; Job, Veronika (Frontiers in Psychology, 2020)
Is the way that kindergarteners view their willpower—as a limited or as a nonlimited resource—related to their motivation and behavioral self-regulation? This study is the first to examine the structure of beliefs about willpower in relation to behavioral self-regulation by interviewing 147 kindergarteners (52% girls) aged 5 to 7 years (M = 6.47, SD = 0.39). A new instrument was developed to assess implicit theories about willpower for this specific age group. Results indicated that kindergarteners who think of their willpower as a nonlimited resource showed better behavioral self-regulation than children who adopted a limited theory, even when controlling for age and gender. Mediation and moderation analyses showed that this relation was partly mediated through the children’s willingness to invest effort to reach a learning goal and that a nonlimited theory was especially beneficial for low achieving children. Findings suggest that fostering metacognitive beliefs in children, such as the belief that willpower is a nonlimited resource, may foster behavioral self-regulation for successful adjustment to the demands of kindergarten and school.